2016
DOI: 10.1128/aac.01121-16
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Two Multidrug-Resistant IncA/C Plasmids from the 1960s by Using the MinION Sequencer Device

Abstract: Two A/C incompatibility group (IncA/C family) plasmids from the 1960s have been sequenced and classified into the A/C 2 type 1 group. R16a and IP40a contain novel antibiotic resistance islands and a complete GIsul2 genomic island not previously found in the family. In the 173.1-kb R16a, the 29.9-kb antibiotic resistance island (ARI) is located in a unique backbone position not utilized by ARIs. ARI R16a consists of Tn1, Tn6020, and Tn6333, harboring the resistance genes bla TEM-1D and aphA1b and a mer module, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 44 publications
(38 reference statements)
2
18
0
Order By: Relevance
“…The remaining two base pair differences result in the leucine usually found at position 113 of Int being replaced with an arginine, and the lysine at position 293 of Dcm3 being replaced with an arginine. The same study also reported the sequence of R16a (Szabo et al, 2016), recovered three years earlier in 1966, from the St-Antoine Hospital in Paris (Chabbert et al, 1972). This type 1 IncC plasmid also includes a complete copy of GIsul2 and does not contain an ARI-A island.…”
Section: Distribution Of Gisul2mentioning
confidence: 72%
See 1 more Smart Citation
“…The remaining two base pair differences result in the leucine usually found at position 113 of Int being replaced with an arginine, and the lysine at position 293 of Dcm3 being replaced with an arginine. The same study also reported the sequence of R16a (Szabo et al, 2016), recovered three years earlier in 1966, from the St-Antoine Hospital in Paris (Chabbert et al, 1972). This type 1 IncC plasmid also includes a complete copy of GIsul2 and does not contain an ARI-A island.…”
Section: Distribution Of Gisul2mentioning
confidence: 72%
“…Subsequent to the release of our pIP40a sequence (Harmer and Hall, 2016), another pIP40a sequence was reported (Szabo et al, 2016) (GenBank accession number KX156772). Interestingly, whilst the sequences are very similar, there are some differences that are likely to have accumulated over time, during storage and passage of the plasmid in different laboratories.…”
Section: Distribution Of Gisul2mentioning
confidence: 99%
“…RP4 was isolated from Pseudomonas aeruginosa (Datta et al, 1971), R1 from Salmonella enterica serovar paratyphi (Anderson and Datta, 1965) and R16a from Providencia stuartii (Chabbert et al, 1972). The three plasmids are low copy number (Grinsted et al, 1972;Uhlin and Nordstrom, 1975;Szabo et al, 2016) and encode TEM βlactamases (Matthew and Hedges, 1976;Szabo et al, 2016), so the three enzymes are very similar. It has been reported that the level of transcription of RP4 β-lactamase is higher than that of R1 plasmid (Crowlesmith and Howe, 1980), which explains the higher levels of protection displayed by RP4 in our results and the predominance of RP4 in our stepwise analysis (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The Oxford Nanopore Technologies (ONT) MinION sequencer is a compact device that produces sequencing reads that are thousands to hundreds of thousands of nucleotides in length with real-time, read-by-read data availability (6). This rapid sequencing technology has many promising applications for the clinical microbiology laboratory and has been used successfully to sequence genomes of viruses, bacteria, and fungi (7)(8)(9)(10)(11)(12)(13)(14), to identify viruses and bacteria in primary clinical specimens (15)(16)(17)(18)(19)(20)(21), and to characterize AMR genes in bacterial isolates and primary specimens (7,9,17,(20)(21)(22)(23)(24). Though MinION single-read error rates are higher than those for Illumina short reads, higher accuracy can be achieved by generating consensus sequences from multiple reads or by complementation with high-accuracy short reads (5,6,8,9,25,26).…”
mentioning
confidence: 99%